Analysis of Coir Fiber/Wood Paint as Composite Anti-Weathering Coatings on Traditional Fishing Boats (Universitas Muhammadiyah Yogyakarta, 2023)
The low resistance of wood as a frame material for traditional fishing boats against splashing sea water, humidity, and high-temperature fluctuations was studied in this study by adding coconut coir fiber to wood paint, where this mixture will become an anti-weathering composite material. To make compatibility between the fibers from coir which are water-absorbing (hydrophilic) and alkyd paints which are water-repellent (hydrophobic), the author gives special treatment to the coco fibers through an acetone pre-treatment process and hot alkali (hot alkali treatment) by soaking fiber in 10% high-temperature sodium hydroxide NaOH solution. Soaking in this solution is able to modify fibers that have a rough surface and reduce hydrogen bonding thereby improving the interfacial bond between the fiber and the filler in the composite. The results obtained were that the addition of fiber with a weight fraction of 3.40% to the alkyd paint matrix made the composite the most optimal anti-weathering coating.